ANALYSIS OF MOISTURE CONTENT, CALORIFIC VALUE AND BURNING RATE OF CORNCOB AND KAPOK RANDU (Ceiba pentranda) SKIN BRIQUETTE - Anshori Huroeroh; Sheilla Rully Anggita; Hamdan Hadi Kusuma (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
Bio charcoal Briquette is a product made from biomass with a carbonization process and compressed with a certain shape. This study aims to examine the calorific value and burning rate of corncob and kapok randu (Ceiba Pentranda) randu (Ceiba pentranda) skin briquettes with variations in the composition of ingredients. The briquette were produced in 5 stages: First, the main material for cobs and kapok randu (Ceiba Pentranda) randu skin is dried in the sun for 3 days so that the weight of the ingredients is reduced by 20%. Second, the carbonization of the main material with a temperature of 400˚C for 60 minutes with a furnace and then materials that has been crushed is sieved with a sieve 50 mesh. Third, compressed briquettes with corncob composition and kapok randu (Ceiba Pentranda) skin in the following ratios of A (100%: 0%), B (75%: 25%), C (50%: 50%), D (25%: 75 %), E (0%: 100%) with 10% w/w tapioca starch as binder. Fourth, the dry the briquette under the sun for 3 days (20 hours) and roasted with a temperature of 100˚C for 60 minutes. Fifth, after dried, the samples were then characterized their moisture content, calorific value, and burning rate. The results show that the highest moisture content value in sample E is 3.3303% and the lowest moisture content in sample B (2.4587%). The highest calorific values are sample E which is 6195.05 Cal / grams. While the lowest calorific value was found in sample D (25% corn cobs and 75% kapok randu (Ceiba Pentranda) skin), which was 3803.96 Cal / grams. The lowest burning rate was found in sample E (100% kapok randu (Ceiba Pentranda) skin) with a value was 0.0448 grams / minute. While the highest burning rate was found in sample D (25% corn cobs and 75% kapok randu (Ceiba Pentranda) skin) with the value was 0.0622 grams/minute.